The Flood Myth in the Traditions of Israel and India - Polish, Daniel
PhD dissertation submitted to the Committee on Higher Degrees in the Study of Religion, Graduate School of Arts and Sciences; Mesopotamian material; Cf. HThR 67 (1974, ersch. 1975) 476-477.